Program penguatan regulasi diri dan orientasi masa depan untuk meningkatkan disiplin serta motivasi pendidikan remaja di Rumah Pelayanan Sosial Wira Adhi Karya - Amalia Sarifatussalma; Rina Umiati; Chamilul Hikam Al Karim (CV Rezki Media, 2026)
Adolescence is a crucial transitional period leading into adulthood. Adolescents, especially those in vulnerable socioeconomic circumstances, tend to experience challenges related to self-regulation. A program focused on strengthening self-regulation and future planning was implemented to improve discipline and motivation to learn among adolescent beneficiaries at the Wira Adhi Karya Social Service Center. These activities aim to help participants recognize their potential, develop plans, and manage their emotions more adaptively. The methods used include psychoeducation, interactive discussions, educational games, and reflection sessions involving 20 participants. The program was implemented through two main activities: PATHFINDER: Discovering Direction and Designing the Future, and Emotion Smart: Recognize–Control–Express. The program’s effectiveness was evaluated through post-activity interviews to assess participants’ understanding. The results showed an increase in participants’ understanding of how to recognize their own potential, set future goals, and understand emotion management strategies. The program proved effective in increasing participants’ active engagement in self-regulation and motivation, as well as providing practical insights into self-regulation. However, ongoing support remains necessary to ensure participants can consistently apply these skills in their daily lives.